FACTORS AFFECTING LIQUIDITY RISK- AN EMPIRICAL ANALYSIS ON TURKISH BANKING SECTOR - Bade Ekim Kocaman; Şenol Babuşcu; Adalet Hazar (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The aim of this study is to determine the factors affecting the liquidity risk of deposit banks in Turkey. In this context, 10 deposit banks with the highest asset size according to their 2020 end of year financial tables were included to the sample and the quarterly data for the 2010-2020 period were tested by static panel data analysis. According to the model results, it is determined that "Equity / Total Assets", "Money Market Funds/Total Assets" and "Inflation" variables affect the liquidity risk. It is also important and specific for the study that the “Money Market Funds/Total Assets” ratio is a determining factor in the liquidity risk, in terms of the literature contribution of the study.